Development of an analytical method for the quantification of bioactive phenolic compounds in grapes and juices. - Canedo-Reis, N.A.P. (2018)
Phenolic compounds, largely present in grapes, have demonstrated a high antioxidant capacity, which is intimately linked to their nutraceutical value.